Assessment of the directions and causes of migration in the modern world - E. S. Lezin (Путеводитель предпринимателя)
The article deals with the essence of migration processes in various theoretical concepts, as well as existing approaches to assessing the impact of labor migration on the state and functioning of the labor market. The author has made a scientific assumption about the need to assess the dependence of the scale of labor migration on socio–economic factors of the country or region, such as the level of economic development, the level of availability of medical and social services, the level of material well–being, the level of spiritual development.It is assumed that these factors are determined by statistical indicators for the region and should be ranked by an expert survey. Migration assessment makes it possible to predict the number and directions of migration flows and to develop measures of state influence and priorities of migration policy that ensures the economic and national security of the country.